Relationship of Daily Rainfall with Short Duration Rainfall - Adhikari, R N (Annals of Arid Zone, 2016)
An attempt is made to establish a relationship between 50-year return period of daily rainfall and 50-year rsturn period of various short duration rainfall for lower Godavari basin considering altitude of stations and distance from are the sea as additional parameters. The regression equations developed based on 9 self recording rain gauge data and tested on data of 5 independent stations randomly selected in the same region.